Pengaruh Cara Pengolahan Umbi Tire (Amorphophallus sp.) terhadap Kadar Kalsium Oksalat - Syamsiah, . (Fakultas MIPA UNM, 2011)
The influence of processing method of tire tuber (Amorphophallus sp.) toward the level of calcium oxalate at Faculty of Mathematics and Natural Sciences, State University of Makassar was to finding out the effect of tuber processing methods tire against calcium oxalate and know the best way of processing. This research conducted in experiment central laboratory of the Ministry of Health, Indonesia, and Makassar. This research consisted of the dependent variable in the form of calcium oxalate in the tuber tire and independent variables such as processing methods. Samples were tire tuber (Amorphophallus sp.) processed by boiling it (A1), salt-water immersion (A2), and wood ash (A3). The research data obtained using titrimetry. Data were analyzed using inferential analysis technique and LSD test at 0.05 significance level. Average-content of calcium oxalate of tire tuber weighing one gram for A0, A1, A2, and A3 respectively was 0.056%, 0.008%, 0.034%, and 0.040%. From the data, it appears there was the influence of processing methods, both those treated with boiling water immersion salt and wood ashes, on serum calcium oxalate in the tuber tire. The most effective way of processing was to reduce or minimize calcium oxalate in the tuber tire processing by boiling.Â